KEBERHASILAN PENEMPATAN KERJA BERDASARKAN PADA KECERDASAN INTELEKTUAL (IQ) DAN MOTIVASI DIRI DI POLITEKNIK LP3I JAKARTA - Rahayu Tri Utami; rahmi rosita (JURNAL LENTERA BISNIS, 2019)
Placement is a very decisive process in getting employees in accordance with what is needed by the company, because the right placement of employees in a position will be able to assist the company in achieving the expected goals. The method used in this method is an evaluation research method which means "decision making process, which is to compare an event, activity, product with predetermined standards and programs. Evaluation as a research means that it will function to explain the phenomenon (Riduwan (2004: 53). Because the value of t arithmetic t value of t table or 4,645 ≥ 1.65, then Ho is rejected, meaning intellectual intelligence really has a significant effect on work placement. Because the value of t count ≥ value of t table or 2.168 ≥ 1.65, then Ho is rejected, meaning self-motivation really has a significant effect on work placement. The magnitude of the effect simultaneously between the variables of intellectual intelligence (X1) and self-motivation (X2) on work placement (Y) is classified as moderate. While contributing together (simultaneous) variables X1, X2 to Y = R2 x 100% or 0.4222 x 100% = 17.8% while the remaining 49.4% is determined by other variables. Then regarding the ups and downs or the size of the work placement can be predicted through the regression equation Y = 22.42 + 0.410X1 + 0.455X2Key Words: occupation, intellectual intelligence (IQ), self motivation